Internalisasi Nilai-nilai Multikultural dalam Tafsîr Al-Rāzi pada Pengembangan Pendekatan Pembelajaran Tafsir - M.Noor Hidayat (Jurnal Studi Agama dan Masyarakat, 2015)
This article contains about study of multicultural values in the tafsîr Imām Fakhruddîn Al-Rāzî (Mafātîḥul Ghaib), which has different specification from other tafsir in the same era. It includes many arguments about theology and fiqh. Furthermore, the multicultural values in this tafsîr are implemented on the development approach of learning tafsîr. This study used library research with phenomenology approach by seeing the reality of tafsîr Imām Fakhruddîn Ar-Rāzî which is accepted and refered by many of firqah, besides tafsîr Maudhū’i is used tool to make the study of tafsir Imām Fakhruddîn Ar-Rāzî deeper. The result of this study consist of two parts: 1) An explanation of multicultural values concepts in tafsîr Mafātîḥul Ghaib, 2) Multicultural approach learning as the result of implementing multicultural values on learning approach.